Designing for digital reading - Pearson, Jennifer, 1984-; Buchanan, George, 1969-; Thimbleby, Harold ([San Rafael, California] : Morgan & Claypool Publishers, 2014)
Reading is a complex human activity that has evolved, and co-evolved, with technology over thousands of years. Mass printing in the fifteenth century firmly established what we know as the modern book, with its physical format of covers and paper pages, and now-standard features such as page numbers, footnotes, and diagrams. Today, electronic documents are enabling paperless reading supported by eReading technologies such as Kindles and Nooks, yet a high proportion of users still opt to print on paper before reading. This persistent habit of'printing to read' is one sign of the shortcomings of digital documents--although the popularity of eReaders is one sign of the shortcomings of paper. How do we get the best of both worlds? The physical properties of paper (for example, it is light, thin, and flexible) contribute to the ease with which physical documents are manipulated; but these properties have a completely different set of affordances to their digital equivalents. Paper can be folded, ripped, or scribbled on almost subconsciously--activities that require significant cognitive attention in their digital form, if they are even possible. The nearly subliminal interaction that comes from years of learned behavior with paper has been described as lightweight interaction, which is achieved when a person actively reads an article in a way that is so easy and unselfconscious that they are not apt to remember their actions later.
5. Improving digital reading -- 5.1 Overview -- 5.2 Running themes -- 5.2.1 Additional space -- 5.2.2 Visual language -- 5.2.3 Immediacy of access -- 5.2.4 Digital technologies -- 5.2.5 Designing for appropriation -- 5.2.6 Completeness of metaphors -- 5.3 The book metaphor -- 5.4 Electronic documents -- 5.5 Concluding remarks.
Includes bibliographical references (pages 105-114).
Compendex
INSPEC
Google scholar
Google book search
Print version record.
Keywords: Reading; Reading -- Research